Pengembangan Asesmen Afektif dan Psikomotor pada Praktikum Kimia Dasar di Sekolah Tinggi Perikanan (STP) Hatta-Sjahrir Banda Naira - Fadli, Muhammad; Mansyur, Mansyur; Salempa, Pince (Chemistry Education Review (CER), 2022)
The study aims to develop affective and psychomotor assessment tools in basic chemistry practicum which are valid, reliable, and practical. The study refers to ADDIE development model which consists of the analysis phase, design phase, development phase, implementation, and evaluation. The implementation process was conducted for students who program basic chemistry subject at STP Hatta-Sjahrir Banda Naira. By considering the criticisms and suggestions from the validator, it is obtained a valid and usable affective and psychomotor assessment tools. The reliability was obtained after being analyzed with SPSS version 21 Cronbach's Alpha value for the assessment tools which were 0.811 and 0.923. The results of the analysis of the responses of the 4 practicum assistants conducted after the practicum activities were completed and observations made at each practicum meeting showed that the average scores obtained were 69.75 and 3.8. The results showed that the affective and psychomotor assessment tools in basic chemistry practicum were declared as valid, reliable, and practical to be used.